Uniform estimates for monotonic polynomial approximation - Dzyubenko, H. A.; Listopad, V. V.; Shevchuk, I. A. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The uniform estimate is established for a monotone polynomial approximation of functions whose smoothness decreases at the ends of a segment.